IMPLIKASI HUKUM TERHADAP ANAK HASIL PERKAWINAN MUT’AH : PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA - Muhamad Rizki Aditya; Ahmad 'Ubaydi Hasbillah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine and analyze the legal status of children born from mut'ah marriages according to the perspective of Islamic law and positive law in Indonesia. Mut'ah marriage is a form of marriage with a certain period of time which in the majority of views of scholars and law in Indonesia is considered invalid. Problems arise when children are born from this relationship, thus giving rise to various legal implications, especially in terms of lineage status, civil rights, and child protection. The research method used is normative law with a statutory approach. The data sources used include primary and secondary legal literature, such as the Qur'an, Hadith, Marriage Law, Compilation of Islamic Law, and Child Protection Law. The results of the study indicate that in Islamic law, children from mut'ah marriages are generally not recognized as legitimate children who have a lineage relationship with their father, except according to the Shia school of thought. Meanwhile, in positive law in Indonesia, children born outside of marriage only have a civil relationship with their mother and their mother's family, as regulated in Article 43 of the Marriage Law. However, the Child Protection Law still emphasizes that every child has the right to receive protection and fulfillment of their rights without discrimination. Therefore, even though the parents' marital status is invalid, the child's rights must still be fulfilled for the sake of justice and humanity